Penyelesaian Sengketa Melalui Upaya Litigasi di Bidang Penegakan Hukum Lingkungan Keperdataan - I Ketut Tjukup; I Gusti Ayu Agung Ari Krisnawati (Departemen Hukum Perdata, 2018)
Environmental dispute settlement through litigation lines is strictly regulated in Law No. 32 of 2009 on the Protection and Environmental Management. The former law pointed HIR and RBg, PERMA No. 1 2002 Event Class Action. HIR and RBg did not set a class action, strict liability, legal standing, citizen lawsuit. Rules pluralistic difﬁ cult as the legal basis of environmental law dispute resolution. Problematic in civil law will cause blurring of norms, conﬂict norms, norms vacancy, will bring the consequences of law enforcers. If the law enforcement believes the law is the law, so that the rule of law, justice, expediency, which is the purpose of the law, it is difﬁ cult to realize. Based on legal issues cause problems pluralistic level, the rules, while the class action always demands are not accepted on the grounds HIR, RBg not set. Based on juridical issues, sociological and philosophical issue of whether arrangements formulated civil judicial procedure in civil Environmental Law Enforcement has been inadequate. Normative legal research writing method and in qualitative analysis to obtain quality legal materials. According to Law No. 48 the Year 2009 on Judicial Power, with the principle of ius curia Novit, a judge can do rechtsvinding. The rule of law in the enforcement raises multi pluralistic interpretation.Keywords: